Gut microbiota modulate host immune cells in cancer development and growth - Erdman, Susan E. (Free Radic Biol Med, 2016)
Emerging evidence shows that microbe interactions with the host immune system impact diverse aspects of cancer development and treatment. As a result, exciting new opportunities exist for engineering diets and microbe cocktails to lower cancer risks with fewer adverse clinical effects than traditional strategies. Microbe-based therapies may ultimately be used to reinforce host immune balance and extinguish cancer for generations to come.